Effect of chronic khat (Catha edulis, Forsk) use on outcome of Plasmodium berghei ANKA infection in Swiss albino mice - Ketema, Tsige (BMC Infect Dis, 2015)
BACKGROUND: The objective of this study was to explore effects of khat (Catha edulis) on outcome of rodent malaria infection and its anti-plasmodial activities on Plasmodium berghei ANKA (PbA). METHODS: Female Swiss albino mice were orally treated with crude khat (Catha edulis) extracts (100, 200 and 300 mg/kg) on a daily basis for 4 weeks prior to PbA infection. Physical, clinical, hematological, biochemical and histo-pathological features of the mice were assessed. In addition, in vivo anti-plasmodial activities of khat were evaluated. RESULTS: The finding of this study showed that khat use was strongly associated with increment of levels of liver and kidney biomarkers, leucopenia, severe anemia, rise in level of inflammation biomarkers: C-reactive protein (CRP), uric acid (UA), increased monocyte-lymphocyte count ratio (MLCR), manifestation of cerebral malaria symptoms such as ataxia, paralysis and deviation of the head but with no pulmonary edema. Significantly lower level of parasitemia (P < 0.05), rectal temperature, but, high level of hemoglobin were observed at the early stage of the PbA infection in khat treated mice than the control. With extension of the treatment period, however, drastic increments were observed in parasite load and rectal temperature although there was reduction in hemoglobin (Hb) level. Moreover, khat showed poor anti-plasmodial activity with <10% parasite suppression activity and lack protection against major malaria symptoms. The significant reduction (P < 0.01) of hematological parameters during PbA infection strengthen the notion that hematological parameters could be good predictors of severe malaria complications in human. CONCLUSIONS: In mice model treated with khat prior to infection with the rodent malaria parasite, khat was found to worsen manifestation of most malaria complications. Furthermore, the same plant showed poor in vivo anti-plasmodial activity and protection against major malaria symptoms.